The Effect of Trust and Habit in Using Digital Technology on Online Shopping Intentions - Yohannes Vemberi; Lucia Ika Fitriastuti (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2023)
The development of digital technology in the world and Indonesia is growing rapidly. The advancement of digital technology has finally made people have the habit of doing online shopping. It is possible that trust and habits of using digital technology influence online shopping intentions. The purpose of this study was to examine the effect of trust and habits of using digital technology on online shopping intentions either partially or simultaneously. Methods of data collection using a questionnaire. The number of samples is 101. The analysis used is multiple linear regression. The tests used to test the hypothesis are the t-test, F test, R2 test. The main finding of this study is that the Trust Variable affects Online Shopping Intentions. Variables of Digital Technology Usage Habits Affect Online Shopping Intentions. The variables of trust and the habit of using digital technology simultaneously affect online shopping intentions. Adjusted R2 obtained by 0.647 means that Trust and Habits of Using Digital Technology affect online shopping intentions by 64.7%, and the remaining 35.3% is influenced by other variables. This research can be developed further by testing other variables such as digital literacy variables, price variables, convenience variables, and others.